Contributions toward a monograph of norantea complex (marcgraviaceae, ericales): validation of four new species for marcgraviastrum (2006)
Four new species of Marcgraviastrum are validated. The new species areMarcgraviastrum apaporensis (endemic to the Colombian Amazonia), M.glossostipum (endemic to Ecuador), M. grandiflorum (endemic to the PeruvianAmazonia), and M. vogelii (endemic to Colombia). On the basis of few collectionsof the genus Marcgraviastrum, we suppose that the species are very rare, causedprincipally, by deforestation of the forests in recent years